2013
DOI: 10.1007/s00018-013-1334-0
|View full text |Cite|
|
Sign up to set email alerts
|

Two types of muscarinic acetylcholine receptors in Drosophila and other arthropods

Abstract: Muscarinic acetylcholine receptors (mAChRs) play a central role in the mammalian nervous system. These receptors are G protein-coupled receptors (GPCRs), which are activated by the agonists acetylcholine and muscarine, and blocked by a variety of antagonists. Mammals have five mAChRs (m1-m5). In this study, we cloned two structurally related GPCRs from the fruit fly Drosophila melanogaster, which, after expression in Chinese hamster ovary cells, proved to be muscarinic acetylcholine receptors. One mAChR (the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 24 publications
10
100
1
Order By: Relevance
“…Similarly, in Hydra, there are also ample immunohistochemical, biochemical and functional data to indicate their presence (Kass-Simon and Pierobon, 2007;Pierobon, 2012) and two putative metabotropic acetylcholine receptors (mAchRs) have been identified (Collin et al, 2013). Ionotropic receptors for small-molecule transmitters have, however, not been studied at the molecular level in Hydra (see below); we will therefore concentrate our discussion of neurotransmitters on neuropeptides.…”
Section: Neurotransmitters In Hydra -Small Molecules and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Hydra, there are also ample immunohistochemical, biochemical and functional data to indicate their presence (Kass-Simon and Pierobon, 2007;Pierobon, 2012) and two putative metabotropic acetylcholine receptors (mAchRs) have been identified (Collin et al, 2013). Ionotropic receptors for small-molecule transmitters have, however, not been studied at the molecular level in Hydra (see below); we will therefore concentrate our discussion of neurotransmitters on neuropeptides.…”
Section: Neurotransmitters In Hydra -Small Molecules and Peptidesmentioning
confidence: 99%
“…The genome of H. magnipapillata contains two mAchRs (Collin et al, 2013) and 17 genes coding for nicotinic acetylcholine receptor (nAchR) subunits , strongly suggesting that H. magnipapillata uses acetylcholine for fast transmission. Expression of five of the nAchRs could be detected by RT-PCR, revealing a predominant expression in the head region.…”
Section: Ion Channel Receptors For Small Molecule Transmitters In Hydmentioning
confidence: 99%
“…We have recently found that Drosophila melanogaster and other insects have two types of mAChRs, named A and B. The A-type mAChRs are pharmacologically very similar to the mammalian m1-m5 receptors, being activated by the agonists acetylcholine and muscarine and inhibited by the antagonists atropine, 3-quinuclidinylbenzilate (QNB), and scopolamine [5]. The B-type mAChRs, however, have a pharmacology that is quite different from the mammalian mAChRs.…”
Section: Introductionmentioning
confidence: 98%
“…The B-type mAChRs, however, have a pharmacology that is quite different from the mammalian mAChRs. They have a high sensitivity to acetylcholine, but a 1000-fold lower sensitivity to muscarine than the A-type receptors and are not blocked by the classical antagonists [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine increases the burst frequency in active preparations that show rhythmic bursts of motor neurone spikes. Because muscarinic receptors belong to a superfamily of G-protein-coupled receptors (Collin et al, 2013), carbachol could induce rhythmic bursts of motor neurone spikes via the activation of cAMP. The finding in this study that the burst frequency of the swimmeret motor neurones elicited by cAMP was facilitated by co-application of L-arginine suggests that the NO-cGMP signaling pathway affects cAMP activity.…”
Section: Research Articlementioning
confidence: 99%